The becoming-photographic of cinema. (1st December 2015) - Colebrook, Claire
Both Gilles Deleuze and Bernard Stiegler have sought a renewal of life, perception and philosophy by way of the radical temporality of cinema. In doing so they have, in part, contributed to a long-standing moralism in philosophy that defines itself against the still or photographic image. Rather than see photography as a fragment of a flow of time, and therefore as on its way to becoming cinematic, I argue that the photograph that is cut off from the flow of time provides a more provocative and post-moral way of approaching the relation between philosophy and the arts.